2010
DOI: 10.1590/s1414-32832010005000035
|View full text |Cite
|
Sign up to set email alerts
|

Violência institucional em maternidades públicas sob a ótica das usuárias

Abstract: Este artigo apresenta e discute os dados de uma pesquisa sobre violência institucional em maternidades públicas, realizada no município de São Paulo. Foram entrevistadas 21 puérperas, com roteiro semiestruturado contando com questões sobre experiências de parto e assistência recebida. Os dados revelaram que as entrevistadas relatam e reconhecem práticas discriminatórias e tratamento grosseiro no âmbito da assistência em maternidades públicas, reagindo com estratégias de resistência ou de acomodação. Essas expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
65

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(101 citation statements)
references
References 17 publications
1
35
0
65
Order By: Relevance
“…Studies on healthcare provision to hypertensive pregnant women correlate the inadequacy of prenatal care mainly to professional fault, at the technical or human relations plan 9,16 . Prejudiced and authoritarian practices, with class and gender biases, towards the clinical conditions and reproductive intentions of women in this study were also reported in a study on institutional violence in public maternity hospitals 18 . The disrespect with sexual and reproductive rights and the imposition of standards and moral values presented by professionals are aspects of institutional violence against women 19 .…”
Section: Comunicação Saúde Educaçãosupporting
confidence: 74%
See 1 more Smart Citation
“…Studies on healthcare provision to hypertensive pregnant women correlate the inadequacy of prenatal care mainly to professional fault, at the technical or human relations plan 9,16 . Prejudiced and authoritarian practices, with class and gender biases, towards the clinical conditions and reproductive intentions of women in this study were also reported in a study on institutional violence in public maternity hospitals 18 . The disrespect with sexual and reproductive rights and the imposition of standards and moral values presented by professionals are aspects of institutional violence against women 19 .…”
Section: Comunicação Saúde Educaçãosupporting
confidence: 74%
“…In Brazil, official data show an important prevalence of hypertension in women at reproductive age, representing 9.7% women between [18][19][20][21][22][23][24]15.4% between 25-34 and 21% between 35-44 years old 3 . Chronic hypertension and history of hypertensive disorders in previous pregnancy represent reproductive risk and require total attention to reproductive health before, during and after pregnancy.…”
Section: Comunicação Saúde Educaçãomentioning
confidence: 99%
“…Outra questão a se considerar, também apontada por Schraiber 19 , é a preocupação maior dos profissionais com seu próprio desempenho, desde o acerto diagnóstico ao uso correto das tecnologias materiais, do que a preocupação com a colaboração da paciente como uma forma de somar o outro em seu desempenho de médi-co. Ao contrário, como os presentes resultados apontam o sentido dado pelos profissionais à noção de "colaboração" por parte das pacientes é o de sua negação, isto é, colaborariam as que abdicam de se expressar, transformadas em corpos dóceis e submissos à intervenção unilateral. Para as demandas da própria paciente, como seria o caso da analgesia de parto, ou da maior participação e conhecimento das intervenções, como o monitoramento do desenvolvimento da dilatação uterina, ou da presença de acompanhantes, não há intervenção oferecida, e por vezes estas demandas, além de silenciadas, sofrem represálias 21 .…”
Section: Considerações Finaisunclassified
“…In many countries, religious influences on health care and the notion that suffering in childbirth is a legitimate penalty that women should endure for having sex, contribute to a culture of neglect of maternal rights and wellbeing, to the absence of privacy or comfort measures during labor and birth, to the liberal use of invasive interventions 4,7 , and sometimes to overt hostility and abuse, especially for women at the bottom end of social hierarchies 4,7,8,9,10 .…”
Section: Introductionmentioning
confidence: 99%